Path Analysis on Determinants of Postpartum Bleeding at Dr. Moewardi Hospital, Central Java - Hidayati, Siti Nur; Budihastuti, Uki Retno; Widyaningsih, Vitri (Journal of Maternal and Child Health, 2019)
Background: Postpartum hemorrhage is bleeding that exceeds 500 ml after the baby is born. The main causes of postpartum bleeding are uterine atony, placental retention, birth canal laceration, and blood clotting abnormalities. Predisposing factors of postpartum hemorrhage are age, parity, anemia, premature rupture of membranes, preeclampsia, prolonged labor, uterine overdistention, labor of action, history of previous bleeding, and distance of pregnancy. Postpartum hemorrhage will cause maternal death if it is not treated immediately. This study aimed to analyze the determinants of postpartum hemorrhage. Subjects and Method: This study used observational analytic with a case control approach. The study was conducted at Dr. Moewardi, Central Java, from April to May 2019. The total sample was 225 maternity mothers who were selected based on fixed disease sampling by using a ratio of 1: 2 between the case and control groups. The dependent variable was postpartum bleeding. The independent variables were age, parity, anemia, premature rupture of membranes, preeclampsia, prolonged labor, uterine overdistention, action delivery, obstetric history, uterine atony, placental retention, birth canal laceration, and pregnancy distance. Data collection techniques used secondary data medical record records which were analyzed by using path analysis. Results: Postpartum hemorrhage was directly and positively associated with atonia uterine (b= 2.46; 95% CI= 1.53 to 3.40; p<0.001), vaginal laceration (b= 1.76; 95% CI= 0.78 to 2.75; p <0.001), poor obstetric history (b= 0.93; 95% CI= 0.11 to 1.76; p= 0.026), and type of labor (b= 1.70; 95% CI= 0.94 to 2.46; p <0.001). It was indirectly affected by preeclampsia, parity, prolonged labor, premature rupture of membrane, age, anemia, uterine overdistention, birth spacing, and placental retention. Conclusion: Postpartum hemorrhage is directly and positively associated with atonia uterine, vaginal laceration, poor obstetric history, and type of labor. It is indirectly affected by pre